2023
DOI: 10.3233/wor-220121
|View full text |Cite
|
Sign up to set email alerts
|

The effects of personal protective equipment on heart rate, oxygen consumption and body temperature of firefighters: A systematic review

Abstract: BACKGROUND: Fire extinguishing operations are carried out by firefighters equipped with personal protective equipment (PPE) in dangerous environments. Although PPE protects firefighters, it can affect many physiological parameters. OBJECTIVE: This study aimed to investigate the effects of PPE on firefighters’ heart rate (HR), oxygen consumption (OC) and body temperature (BT). METHODS: This systematic review thoroughly reviewed relevant articles in the reliable databases “Web of Science”, “Embase”, “IranDoc”, “… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…In a similar study, SPO2 levels of 98.57% before wearing PPE decreased to 98.34% with PPE and after the removal of PPE it was 98.39% -without major variation, it remained around 98% [10]. Oxygen consumption have been shown to be increased with wearing a PPE kit [17]. Significantly lower SpO2 in the PPE group compared to the control group across conditions might explain the tiredness or fatigue with PPE use as documented [21], however, it is interesting that overall the levels are in the normal range in our study which might be explained by the less restrictive type of full-body PPE kit.…”
Section: Physiological Variablesmentioning
confidence: 84%
See 1 more Smart Citation
“…In a similar study, SPO2 levels of 98.57% before wearing PPE decreased to 98.34% with PPE and after the removal of PPE it was 98.39% -without major variation, it remained around 98% [10]. Oxygen consumption have been shown to be increased with wearing a PPE kit [17]. Significantly lower SpO2 in the PPE group compared to the control group across conditions might explain the tiredness or fatigue with PPE use as documented [21], however, it is interesting that overall the levels are in the normal range in our study which might be explained by the less restrictive type of full-body PPE kit.…”
Section: Physiological Variablesmentioning
confidence: 84%
“…A minimal change in heart rate or even a linear relationship of heart rate with temperature with or without PPE has been documented [10,12]. A systematic review suggested increase in heart rate with PPE was highly dependent on the weight of the PPE, the type of cloth of PPE and weather conditions [17]. No change in cardiovascular and respiratory parameters was noted with the use of N95 masks in a study of pregnant vs non-pregnant females [18].…”
Section: Physiological Variablesmentioning
confidence: 99%
“…The first step involved compiling a comprehensive list of potential hazards from various sources, including a literature review and interviews with a panel of experts [ [32] , [33] , [34] , [35] , [36] ]. Table 4 shows the findings of identifying 25 important risks.…”
Section: Case Studymentioning
confidence: 99%
“…These substances adversely affect the human body and can cause diseases such as cancer [8][9][10][11][12][13][14][15]. Therefore, the correct use, washing and management of personal protective equipment (PPE) is very important for firefighters engaged in firefighting activities at fire scenes [16][17][18]. The PPE worn by firefighters during fire scenes includes firefighting protective suits (FPSs), self-contained breathing apparatus (SCBA) cylinders, face masks, helmets, firefighting boots and gloves.…”
Section: Introductionmentioning
confidence: 99%